SEGMENTATION OF INNOVATION CAPABILITY IN BATIK SMES USING K-MEANS CLUSTERING - Aditya, Reza; Achmad, Fandi (Politeknik META Industri Cikarang, 2025)
Increasing global competitive pressures and sustainability demands encourage Small and Medium Enterprises (SMEs) to strengthen their Innovation Capability to maintain competitive advantage. In the batik creative industry, innovation capability is not only crucial for increasing competitiveness but also for maintaining the sustainability of cultural heritage. However, the level of Innovation Capability in Batik SMEs is still heterogeneous and has not been systematically mapped using a data-driven approach. This study aims to segment Batik SMEs based on Innovation Capability (IC) using the K-Means Clustering method. This study uses a quantitative approach involving 82 Batik SME owners or managers through a purposive sampling technique. Innovation capability is measured using five indicators (IC1–IC5) covering technology adoption, green process adjustment, customer collaboration, cross-functional coordination, and access to new technologies. Data are standardized using Z-score normalization before the clustering process. The optimal number of clusters is determined using the Elbow and Silhouette Coefficient methods, which produce the two best clusters (silhouette = 0.6179) based on a balance of model quality and interpretability. The research results show two main segments: the High Innovation Capability cluster and the Low Innovation Capability cluster. The High Innovation Capability cluster demonstrates superior performance across all indicators, particularly in process adaptation and cross-functional coordination. Conversely, the Low Innovation Capability cluster has limitations in technology adoption and access to innovation-supporting technologies. This research provides a theoretical contribution to strengthening the literature on innovation capability based on data segmentation in SMEs, as well as a practical contribution to formulating more targeted sustainability strategies.Keywords: Capability Innovation; Batik SMEs; Sustainability; Data-Based Segmentation; Clustering